The impact of climate change on a cost-optimal highly renewable European electricity network. (15th November 2018) - Schlott, Markus; Kies, Alexander; Brown, Tom; Schramm, Stefan; Greiner, Martin
Highlights: Effect of climate change in an strong climate change (RCP 8.5) scenario studied using various EURO-Cordex ensemble members. Differences in capacity factors for wind and solar PV are stronger emphasized due to climate change. System costs increase until the end of the century by around 5% driven by a higher share of solar PV. Abstract: We use three ensemble members of the EURO-CORDEX project and their data on surface wind speeds, solar irradiation as well as water runoff with a spatial resolution of 12 km and a temporal resolution of 3 h under representative concentration pathway 8.5 (associated with a strong climate change and a temperature increase of 2.6–4.8 °C until the end of the century) until 2100 to investigate the impact of climate change on wind, solar and hydro resources and consequently on a highly renewable and cost-optimal European power system. The weather data is transformed into power, different aspects such as capacity factors and correlation lengths are investigated and the resulting implications for the European power system are discussed. In addition, we compare a 30-node model of Europe with historical and climate change-affected data, where investments in generation, transmission and storage facilities are optimised. Differences in capacity factors among European countries are more strongly emphasized at the end of the century compared to historic data. This results in a significantly increased photovoltaic share in the cost-optimal power system. In addition, annual hydro inflow patterns of major hydro producers change considerably. System costs increase by 5% until the end of the century and the impact of climate change on these costs is of similar magnitude as differences between the ensemble members. The results show that including climate affected-weather data in power system simulations of the future has an observable effect.